Assessment of Unmanned Vehicle (UxV) Control Interfaces Using a Holistic Usability Method. (September 2014) - Proaps, Alexandra B.; Chancey, Eric T.; Bliss, James P.; Crane, Peter
The primary purpose of this project was to objectively assess the usability of two proprietary control interfaces for UxV operation. Interface evaluations frequently rely on subjective measures and (to a lesser degree) operational performance to judge quality and usability. The concept of performance is often multidimensional, particularly in the case of unmanned vehicle (UxV) operation. We adopt a more holistic approach to usability by triangulating physiological, performance, and subjective data to better consider both cognitive and performance attributes of performance. To assess usability and performance aspects associated with the two candidate UxV control interfaces, we have completed multiple efforts. After completing a thorough literature review, a cognitive task analysis, and multiple heuristic evaluations of our data logging software and the interfaces to be evaluated, we pilot tested one interface with novices and experts using our proposed usability method. This paper serves as an overview of our usability testing method which includes subjective, physiological, and performance assessments of error rates, workload, stress, attention, ease of use, and learnability. We present some initial conclusions from our pilot test using expert military UxV and novice operators. Finally, we present initial evidence for the success of our usability approach.